Predstavitev spletnih strani Začetno in nadaljevalno učenje plavanja - Kapus, Jernej (Šport (Ljubljana), 2013)
This year two websites were launched, namely Beginnerćs Learning of Swimming (http://eucenje.fakultetazasport.si/plavanje1. php) and Intermediate Learning of Swimming (http://eucenje.fakultetazasport.si/plavanje2.php) by the authors Jernej Kapus, Dorica Šajber and Igor Štirn, with the technical assistance of Matej Lekše, Rok Vertič and Stanko Štuhec. The purpose of the websites is to present, through film material, the beginner's and intermediate levels of learning to swim. The material is a pictorial supplement to the chapters on swimming techniques, turns and jumps in the water as well as on the methods of beginner's and intermediate swimming lessons from the textbook Swimming, Learning (2001). In the textbook, Venceslav Kapus and his colleagues presented the doctrine of learning to swim in Slovenia at the start of the new millennium.
Keywords: learning; learning to swim; methodical procedure; metodičen postopek; plavanje; sport; šport; učenje